EVALUASI KERUSAKAN PIER JEMBATAN WAIRUATA DAN PENGENDALIAN PENANGANAN DENGAN MUTU BETON K-300 RUAS MASOHI - WAIPIA - Firda; Soumokil Hengky Johny; Selviana Walsen (Journal Agregate, 2023)
Wairuata Bridge was built in 1982, with a type of steel frame bridge, has a span of 60 m, and a length of 160. The bridge suffered damage to a 2m high pier from the height of the 8m stake pole. Take a sampleof the soft aggregate material in times wairuata, and then for the removal ofthe rough aggregate material on wainoa, Waipia – Masohi. The K-300 quality concrete. concrete quality is highly dependent on production and treatmen. Laboratory testing included an examination of graduation, spesific gravity, absorption of mud content, and bulk density. The results of the converted concrete compressive strength on day 28 was 313,77 kg/cm²